2021
DOI: 10.7759/cureus.15600
|View full text |Cite
|
Sign up to set email alerts
|

A Case of COVID-19 Mimicking Acute Appendicitis in Multi-System Inflammatory Syndrome

Abstract: Martin et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, cardiac complications including acute myocardial injury, myocarditis, decreased ejection fraction, coronary artery aneurysm, pericarditis, valve dysfunction, pericardial effusion, arrhythmia, ventricular dilation, and tachycardia are reported ( Panigrahy et al, 2020 ; Pouletty et al, 2020 ; Simpson and Newburger, 2020 ). Many gastrointestinal signs and symptoms of MIS-C overlap with those of acute appendicitis ( Nakra et al, 2020 ; Belay et al, 2021 ; Martin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cardiac complications including acute myocardial injury, myocarditis, decreased ejection fraction, coronary artery aneurysm, pericarditis, valve dysfunction, pericardial effusion, arrhythmia, ventricular dilation, and tachycardia are reported ( Panigrahy et al, 2020 ; Pouletty et al, 2020 ; Simpson and Newburger, 2020 ). Many gastrointestinal signs and symptoms of MIS-C overlap with those of acute appendicitis ( Nakra et al, 2020 ; Belay et al, 2021 ; Martin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The appearance and size of the appendix on USG help us in the diagnosis of AA. Martin et al [8] reported the diameter of the appendix on USG as 7 mm in a case with MIS-C. Jackson et al [9] reported the diameter of the appendix as 9 mm in their case reports. The appendix diameter of this case on USG was 6.8 mm.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several case reports of MIS-C associated with SARS-CoV-2 infection and acute appendicitis (33)(34)(35)(36)(37). These previous findings suggested that it may be difficult to make the differential diagnosis between acute appendicitis and MIS-C, as some patients may have both acute appendicitis and MIS-C, and others may have appendix inflammation (mimicking appendicitis) as gastrointestinal involvement due to MIS-C.…”
Section: Discussionmentioning
confidence: 99%